Client emotional involvement and occurrence of in-session therapeutic phenomena - Fitzpatrick, Marilyn; Peternelli, Loris; Stalikas, Anastassios; Iwakabe, Shigeru (Canadian Journal of Counselling and Psychotherapy, 2007)
This study examined the relationship between changes in the level of client emotional involvement as measured by the Client Experiencing Scale and Strength of Feeling Scale-Revised, and occurrence of in-session therapeutic phenomena as measured by the Category System of Client Good Moments, in Person-Centred and Rational-Emotive Therapy. Judges rated client statements in 6 sessions conducted by Carl Rogers and 6 sessions conducted by Albert Ellis. The findings indicated that: (a) client statements which contained a good-moment had significantly higher levels of client emotional involvement; and (b) there was no difference between therapeutic approaches in the level of client emotional involvement achieved. Implications of the results for theory, practice, and future research are outlined.